Direction selectivity of the retinotectal system of fish: findings based on microelectrode extracellular recordings of the tectum opticum - Damjanović, Ilija; Aliper, Alexey; Maximov, Paul; Zaichikova, Alisa; Gačić, Zoran; Maximova, Elena (Archives of Biological Sciences, 2023)
Paper description: Fish are a convenient model for studying the visual system because of the common variety of visual pigments, regularity of the morphology of the retina, and structural plan of the brain’s visual centers. An understanding of the mechanisms of the visual system and its development and its evolutionary aspect can be gained by combining data obtained using electrophysiology on adults, Ca2+ imaging on transparent larvae of Danio rerio, behavioral experiments and observations of visually guided behavior in the wild. In this review article, our findings are compared with the results of authors examining direction selectivity in the fish retinotectal system. Abstract: Vision in fish plays an important role in different forms of visually guided behavior. The visual system of fish is available for research by different methods; it is a convenient experimental model for studying and understanding the mechanisms of vision in general. Responses of retinal direction-selective (DS) ganglion cells (GCs) are recorded extracellularly from their axon terminals in the superficial layers of the tectum opticum (TO). They can be divided into three distinct groups according to the preferred directions of stimulus movement: caudorostral, dorsoventral and ventrodorsal. Each of these groups comprises both ON and OFF units in equal proportions. Relatively small receptive fields (3-8°) and fine spatial resolution characterize retinal DS units as local motion detectors. Conversely, the responses of direction-selective tectal neurons (DS TNs) are recorded at two different tectal levels, deeper than the zone of retinal DS afferents. They are characterized by large receptive fields (up to 60°) and are indifferent to any sign of contrast, i.e., they can be considered as ON-OFF-type units. Four types of ON-OFF DS TNs preferring different directions of motion have been recorded. The preferred directions of three types of DS TNs match the preferred directions of three types of DS GCs. Matching the three preferred directions of ON and OFF DS GCs and ON-OFF DS TNs has allowed us to hypothesize that the GCs with caudorostral, ventrodorsal and dorsoventral preferences are input neurons for the corresponding types of DS TNs. On the other hand, the rostrocaudal preference in the fourth type of DS TNs, recorded exclusively in the deep tectal zone, is an emergent property of the TO. In this review, our findings are compared with the results of other authors examining direction selectivity in the fish retinotectal system.